Sightings of Orcinus orca (Linnaeus, 1758) (Cetartiodactyla: Odontoceti: Delphinidae) in the Costa Rican Pacific (1990-2020) - Castro-Azofeifa, César (2021)
Orcas are little studied cetaceans in the tropics, and their movements through Costa Rican waters have been scarcely addressed. They are animals of great ecological importance due to their role as top predators and documenting their presence in the country can be of great scientific and social importance, for coastal communities this information could represent a great opportunity from an ecotourism perspective. The objective of this research was to synthesize and systematize the existing reports regarding orcas in the country, using scientific publications, books and information derived from citizen reports. The information collected up to December 31, 2020, was considered. The sightings and the number of killer whales in the Costa Rican Pacific were divided regionally: 17 sightings and 56 individuals for the South Pacific, 7 sightings and 20 individuals for the North Pacific. 3 sightings and 19 individuals in the Central Pacific and 4 sightings and 10 individuals for Isla del Coco. There were 31 sightings and 105 individuals in total. No statistically significant differences were found in the occurrence of killer whales between the zones, although there is a greater number of reports in the South Pacific, especially in September. Studying the presence of orcas in the country, involving processes of environmental education and citizen science, can provide important tools for the formulation of public policies that allow an effective conservation of cetaceans and offer greater opportunities for growth for the ecotourism industry in the coasts.